Generative AI in Capital Markets: Information Production, Dissemination, and Processing - Cao, Sean Shun; Chen, Wilbur Xinyuan; Ma, Guang; Srinivasan, Suraj (Journal of Accounting Research, 2026)
ABSTRACT We synthesize evidence from six papers presented at the 2025 Journal of Accounting Research Conference on how generative artificial intelligence (GenAI) is reshaping capital‐market information flows. Our discussion is organized around an economic framework with three layers: information production by firms and accounting professionals, information dissemination through intermediaries, and information processing by investors. Across these layers, the conference papers show that GenAI can lower preparation costs, improve intermediary productivity, and reduce investors’ processing costs. At the same time, they point to a common constraint: whether GenAI improves the information environment depends critically on information verification costs. We also highlight gaps in current evidence and outline future research opportunities within and across the three layers.